Leveraging Digital and Semiotic Strategies to Enhance Consumer Decisions on Agricultural MSME Products - Kusumawati, Reni Diah; Ikasari, Diana; Humaini, Irfan; Wibowo, Agung Prasetyo; Dutt, Himanshu (Decode: Jurnal Pendidikan Teknologi Informasi, 2025)
This study aims to analyze the influence of digital transformation and marketing strategies on the purchase decisions of products from micro, small, and medium enterprises (MSMEs). Independent variables examined include e-service quality, social media promotion, online payment systems, product quality, and semiotics. A quantitative approach was used with multiple linear regression analysis on data collected via questionnaires. The results show that e-service quality, online payment systems, and semiotics significantly influence agricultural MSME product purchase decisions. Meanwhile, social media promotion and product quality do not show a significant effect. These findings indicate that agricultural MSME product consumers are more influenced by efficient digital experiences, ease in payment systems, and the visual and symbolic elements of products. The insignificance of social media promotion may be due to the still-dominant role of word-of-mouth, while product quality may be assumed to be inherent in the perceived authenticity and trust in local MSMEs. These findings underscore the importance of digital efficiency and visual communication in building emotional consumer experiences. MSMEs need to strengthen their digital service systems, enhance symbolic strategies through semiotics, and obtain policy support for training, mentoring, and brand development in order to remain competitive in the dynamic digital economy era.